Technology start-up marketing strategy and lifecycle: First empirical findings by qualitative research - Jakub Ulč; Miroslav Mandel (Trends Economics and Management, 2021)
Purpose of the article: Technology start-ups go through certain stages in their lifecycle. In each stage of the lifecycle, there is a different approach to marketing strategy and its application through marketing activities. Creating an empirically based framework of a technology startup marketing strategy based on each lifecycle stage will increase the chances of success for such a technology start-up. Methodology: This research is based on qualitative research using structured interviews with the Czech and Slovak technology start-ups. The questions were validated by pilot research with a selected technology start-up and modified accordingly. The sample was obtained using nonprobability sampling methods. Deductive coding and content analysis are used. The outputs are represented by categorisation and followed by summarisation in the empirically based framework. Scientific aim: The aim is to create an empirically based framework of the marketing strategy of a technology start-up based on the lifecycle stages. The empirically based framework will be developed as an initial effort to gain knowledge in this area and to develop questions or the research direction for the future. Findings: The empirically based framework is developed through qualitative research to define the core marketing activities at a specific lifecycle stage. These activities are divided into categories of coding. The technology start-up should immediately and proactively develop marketing activities at the beginning of its foundation, not only internally but also with external support. Conclusions: For boosting the success of a technology start-up, it is necessary to create customised marketing activities. The ambiguous definition of a start-up hinders the advancement of the body of knowledge in this area and therefore primary research methods must be developed. The research is limited by the broad scope of the given topic. The marketing strategy area as such cannot be entirely covered and therefore sub-points need to be further addressed.
Keywords: M13; O32; 650; start-up; technology start-up; start-up development; start-up lifecycle; marketing strategy; marketing mix